ANALYSIS OF REFERENCES IN THE FILM NA WILLA: A PRAGMATIC STUDY - Andi Batara Indra; Diah Kusyani (Program Studi Pendidikan Bahasa Indonesia FKIP-UNIVA Medan, 2026)
This study aims to describe the types and functions of references in the film Na Willa using pragmatic studies. This study uses a qualitative approach with descriptive methods. The data source in this study is the dialogue between characters in the film Na Willa, while the data is in the form of speech containing reference elements. The data collection technique was carried out through listening and note-taking techniques, while the data analysis technique used the pragmatic matching method. The results of the study show that there are three types of references used in the film Na Willa, namely anaphora, cataphora, and exophora references. Anaphora references are the most dominant type used, which function to refer back to previously mentioned elements so as to maintain the cohesion and effectiveness of the speech. Cataphora references are used to provide emphasis and create a dramatic effect by presenting references after reference elements. Meanwhile, exophora references depend on the context of the situation outside the text and are strongly supported by visual elements in the film. The use of references in the film Na Willa plays an important role in building cohesion, clarity of meaning, and the effectiveness of communication in dialogue. This research is expected to contribute to the development of pragmatic studies, especially in the analysis of references in audiovisual media.